PENGARUH KOMITE AUDIT DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PRAKTIK PENGHINDARAN PAJAK PERUSAHAAN - Pratiwi, Sri Nahda Rizky; Restuti, Mitha Dwi (E-Jurnal Akuntansi TSM, 2025)
The function of audit committee is to avoid deviant actions related to financial reports, including minimizing tax avoidance practices in companies. Corporate social responsibility with the audit committee which has a role in increasing responsibility for the social environment so as to prevent tax avoidance. This research aims to find empirical evidence regarding the influence of the audit committee and corporate social responsibility on tax avoidance practices. The research sample was 114 observations of consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. This research uses linear regression for its analysis. The research results show that the audit committee and corporate social responsibility simultaneously influence tax avoidance practices. Partially, it shows that the audit committee has an influence on tax avoidance practices, while corporate social responsibility has no effect on tax avoidance practices. The lack influence of corporate social responsibility on tax avoidance practices is due to the pandemic which has caused companies to focus on operational activities rather than social activities.